The impact of electrical contacts and contact-induced ultralow noise amplitudes in layered transistors. (20th October 2016) - Hsu, Chih-Kai; Lin, Chi-Yi; Li, Wenwu; Sun, Huabin; Xu, Yong; Hu, Zhigao; Chang, Yuan-Ming; Suen, Yuen-Wuu; Lin, Yen-Fu
Abstract: Electrical contacts made of conducting channels with external circuitry significantly impact electronic performances, in particular for two-dimensional semiconductors. This work presents a systematic study of back-to-back Schottky contacts to a layered compound of semiconducting flakes through static and dynamic electrical measurements and the first demonstration of Schottky barrier-dominated, p-type PbSnS2 field-effect transistors. In the static analysis, the Schottky barrier height of the layered transistors can be modulated by applied electrostatic fields, while the contact-dominated fluctuations render to the 1/ f electric noise and induce a normalized noise amplitude in the order of 10 −9 –10 −8 . Such an ultralow-noise amplitude, which is never observed in other layered semiconducting transistors, is ascribed to the existence of Schottky barriers. Our experimental results provide a nuanced perspective for advancing the understanding of performance limit with increasing numbers of layers for electronic development.